Studies on Existing Indigenous Rice Landraces and their Survival Strategies at Old Alluvial Region of North and South Dinajpur, West Bengal, India- A Case Study - Sen, Dhiman; Maity, S. K.; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
The excellent rice biodiversity of old alluvial region of North and South Dinajpur district in West Bengal had a long history and it had been developed through evolutionary process over a long period of time and sustained through ages by maintaining a perfect interaction with the environment and ecosystem. However, that rich rice biodiversity is under threat as most of the varieties are extinct only with some exception. The existing indigenous rice landraces have been studied based on their associated ethnic cultivation techniques, adaptation, stress tolerance, morphological and physiological characters, overall production and current existence status. The landraces are well adapted under various agro-ecological conditions. Diversity can be observed in their morphological and physiological characters, tolerance to stress and response to different traditional agro techniques. The existence of these varieties are either because of their extra ordinary adaptation or stress tolerance character or excellent grain quality and therefore, high market price. Involvement of certain cultivars in ethnic and socio-religious life also plays an important role towards the survival of these landraces under the scenario of a disappearing indigenous rice biodiversity in this region. Suitable market oriented cultivation in terms of organic crop, promoting commercially as holistic food, processed product, aromatic quality rice etc. can increase demand and market price of these cultivars. Side by side, conservation and research work should be enhanced for these underutilized varieties. With such strategies cultivars can find their way of survival.